UPAYA MENINGKATKAN HASIL BELAJAR PKn MENGGUNAKAN MODEL ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION PADA SISWA KELAS VII SMP NEGERI 1 MILA - Vera Yunita; Zulkifli Zulkifli; Nurjannah Nurjannah (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2026)
This study aims to improve student learning outcomes in Civics Education (PKn) through the implementation of the Active Learning model of the Role Reversal Question type for seventh-grade students at SMP Negeri 1 Mila. The method used is Classroom Action Research (CAR), conducted in three cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The subjects in this study were the seventh-grade students of SMP Negeri 1 Mila for the 2024/2025 academic year. The results of the study show an improvement in student learning outcomes from one cycle to the next. In Cycle I, only 11 students (34.375%) achieved mastery. In Cycle II, this increased to 16 students (50%), and in Cycle III, it reached 26 students (81.25%). The class average score also improved, from 64.59 in Cycle I to 72.56 in Cycle II, and continued to increase in Cycle III, exceeding the Minimum Mastery Criteria (KKM). Both teacher and student activities during the learning process also showed improvement, reaching a "good" category. Based on these results, it can be concluded that the Active Learning model of the Role Reversal Question type is effective in improving student learning outcomes in Civics Education. This model encourages students to be more active, confident, and directly involved in the learning process, thereby creating an interactive and enjoyable classroom atmosphere.